Development and Application of Cloud Storage Technology in Video Surveillance - Shan, Dedong (Journal of Artificial Intelligence and Information, 2025)
Through the cloud-based data storage deployment mode, the application of distributed computing methods, a large number of different types of data storage devices in the network through the application software set up, effectively and reasonably unified computing and data processing, End users have centralized access to cloud-stored data resources and business systems through remote or similar software application and program interfaces to enable efficient and fast resource analysis and data processing in large-scale data storage and access environments. Therefore, this article makes a specific analysis on the development and application of cloud storage technology in video surveillance.